Itemized point cost method in human resource cost accounting in medical service projects - Yingqi Li; Siyuan Liang; Kui Qin; Hongtong Su; Peiyong Xia (Cost Effectiveness and Resource Allocation)
Abstract Background The cost accounting of medical service projects forms the basis for disease cost accounting and DRG (Diagnosis-Related Groups) cost accounting. Among the various costs involved, human resources represent a significant portion and are highly complex, making their accurate accounting a critical and challenging aspect of cost accounting for medical service projects. Methods This paper introduces the itemized point cost (IPC) method, a novel cost accounting approach based on the RBRVS (Resource-Based Relative Value Scale) theory. It outlines the core concepts of “points” and “process steps” within the IPC framework and details its application in human cost accounting. An example of impacted tooth extraction in the stomatology department of Hospital A is used to illustrate the IPC method's implementation process. Findings A comparative analysis with activity-based costing and time-estimation costing methods shows that the IPC method is concise, practical, and operable. It is also aligned with the principles of cost-effectiveness. Conclusions The paper proposes strategies to promote the IPC method, including leveraging information technology, enhancing top-level design, and standardizing processes, to improve its adoption and effectiveness in medical cost accounting.